Bibliometric Review of Research on Green Farming Practices in Agriculture: A Global Literature Overview 2010–2024 - Loso Judijanto (West Science Agro, 2026)
Green farming practices have emerged as a critical approach to addressing the interconnected challenges of food security, environmental degradation, climate change, and sustainable agricultural development. As global interest in environmentally responsible farming continues to expand, a comprehensive understanding of the evolution and intellectual structure of this research field becomes increasingly important. This study aims to examine the development of green farming practices research through a bibliometric analysis of global scientific publications published between 2010 and 2024. Data were collected from the Scopus database and analyzed using bibliometric techniques and VOSviewer to explore publication trends, influential literature, collaboration networks, and thematic developments within the field. The findings reveal a significant growth in research output over the study period, reflecting increasing academic and practical interest in sustainable agriculture. Citation analysis identifies soil health, integrated soil fertility management, agroecology, conservation farming, and food security as the most influential research themes. Co-authorship and country collaboration analyses indicate active international cooperation, with China, India, the Russian Federation, the United States, and several European countries serving as major contributors to the field. Keyword co-occurrence, overlay, and density analyses demonstrate a transition from traditional sustainability-oriented agricultural studies toward technology-driven approaches characterized by artificial intelligence, machine learning, precision agriculture, smart agriculture, Internet of Things (IoT), blockchain, digital transformation, and Agriculture 4.0. The results suggest that future advancements in green farming practices will increasingly rely on the integration of digital technologies and sustainable agricultural principles to enhance productivity, resource efficiency, climate resilience, and food security.